Japan-Indonesia Cooperation in Dealing with the Labour Crisis in Japan - Desyana, Annisa; Jatmika, Sidik (Universitas Muhammadiyah Yogyakarta, 2023)
Despite its successful economy, Japan is facing a labour shortage that threatens the country’s economy. This shortage has led the Japanese government to seek solutions to meet its workforce's needs. In contrast, Indonesia, with its large population, is facing problems with labour market imbalances. In response to the problems, Japan began to establish labour cooperation with Indonesia to address Japan’s labour crisis. Indonesia is currently the third-largest labour-sending country to Japan after Vietnam and the Philippines. This is supported by Indonesia’s labour skills that meet the requirements of work in Japan. Moreover, Japan and Indonesia have a similar culture and manner that makes many Indonesian migrant workers interested in working in Japan, as well as the Japanese community, which easily accepts Indonesian workers in Japan. By utilising the concept of international relations through a qualitative method, a literature study is conducted by gathering information through reports, news articles, and journal articles. This research found that Japan-Indonesia cooperation in dealing with the labour crisis in Japan was carried out by revising the immigration policy by the Japanese government to make it easier for Indonesian workers to enter Japan, providing financial assistance and training to Indonesian workers, and establishing a labour cooperation scheme, namely JIEPA and SSW, between Japan and Indonesia. Furthermore, this study found that there is a technical internship cooperation programme between two countries that is harmful to both Japan and Indonesia.